PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERBASIS GUIDED INQUIRY PADA MATERI BIOPROSES SEL KELAS XI - Atika Rani Oktavianti; Anak Agung Oka; Handoko Santoso (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2023)
This development research aims to produce the products in the form of guided inquiry-based biology learning modules on cell bioprocessing materials that are suitable for use as teaching materials for high school of XI grade. The development of this module uses the R&D development model according to Sugiyono, which starts from searching for potentials and problems, data collection, product design, design validation, design revision, product testing, product revision, trial use, product revision and mass production. The results of the development of guided inquiry-based biology modules from the aspects of design and media obtained a percentage of 80%, the results of the validation of the material aspects obtained a percentage of 93%, the results of validation from the subject teachers obtained a percentage of 89%, and the results of the response of students obtained a percentage of 85 %, and concluded an average percentage value of 86% with the criteria